ASPECTS OF DECARBONIZATION OF THE ELECTRICAL SUPPLY SYSTEM IN THE CONDITIONS OF INDUSTRIAL ENTERPRISES - BOIKO, SERGEY; SHCHOKIN, VADYM; VISHNEVSKYI, SVIATOSLAV; DANILIN, OLEKSANDR; HUSAROVA, OKSANA; HRYBANOVA, SVITLANA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The significant influence of industrial enterprises provokes sharp climatic changes, which are especially felt locally. Such loads on the ecology of the environment, caused by the activities of industrial enterprises, endanger the safe existence of individual biological individuals and the sustainable development of the social economy in the future. One of the important reasons for such changes is the increase in emissions of greenhouse gases, harmful gases and dust. Meanwhile, a number of issues related to the problem of reducing the ecological burden on the environment through decarbonization of Ukraine’s electricity industry remain unresolved. At this stage of implementation, the Smart Grid concept is considered from the point of view of electrical networks, although in the future it will be a combination of electrical, fuel and heat networks. The International Energy Agency sees hydrogen as a link between these networks. The analysis of the possibility and features of the implementation of the concept of decarbonization of power supply systems of industrial enterprises in the aspect of sustainable development showed the relevance of the implementation of distributed generation sources using buffer storage of electric energy in order to stabilize the level of generated electric energy. It is proposed to use solid polymer electrolyzers as buffer accumulators of electric energy generated by sources of distributed generation based on renewable sources.